Delta-Notch signaling is involved in the segregation of the three germ layers in Xenopus laevis - Revinski, Diego Raul (2010)
In vertebrates, the induction of the three germ layers (ectoderm, mesoderm and endoderm) has been extensively studied, but less is known about how they segregate. Here, we investigated whether Delta-Notch signaling is involved in this process. Activating the pathway in the marginal zone with NotchICD resulted in an expansion of endodermal and neural ectoderm precursors, leaving a thinner mesodermal ring around the blastopore at gastrula stage, when germ layers are segregated. On the other hand, when the pathway was blocked with Delta-1STU or with an antisense morpholino oligonucleotide against Notch, the pan-mesodermal brachyury (bra) domain was expanded and the neural border was moved animalwards. Strikingly, the suprablastoporal endoderm was either expanded when Delta-1 signaling was blocked, or reduced after the general knock-down of Notch. In addition, either activating or blocking the pathway delays the blastopore closure. We conclude that the process of delimiting the three germ layers requires Notch signaling, which may be finely regulated by ligands and/or involve non-canonical components of the pathway. Moreover, Notch activity must be modulated at appropriate levels during this process in order to keep normal morphogenetic movements during gastrulation.